Synthesis and characterization of cholesteric thermotropic liquid crystalline polyesters - Jadhav, Sushilkumar A.; Chougule, Rahul R.; Shinde, Yogesh A.; Chavan, Nayaku (Journal of Applied Polymer Science, 2006)
Cholesteric liquid crystalline polyesters were successfully synthesized from isosorbide, methyl hydroquinone, and isophthaloyl chloride. Homo/copolyesters were synthesized by the solution polycondensation method, for which a mild organic base such as pyridine was employed. Inherent viscosities of polyesters P-3-P-5 were in the range of 0.31-0.39 dL/g at 25 degrees C in chloroform, and polyesters P-1 and P-2 were insoluble in chloroform. Homo/copolyesters based on isosorbide, methyl hydroquinone, and isophthalic acid had thermal stability at more than 300 degrees C on the basis of 10% weight loss. The thermotropic liquid crystalline properties were examined by differential scanning calorimetry and polarizing optical microscopy. Wide-angle X-ray diffraction study demonstrated that polyesters P-1, P-2, and P-3 were semicrystalline, whereas the degree of crystallinity of polyesters P-4 and P-5 was less than 5%. Copolyester P-4 showed formation of a yellow iridescent streak at 209 degrees C on heating and development of a Grand-jean texture at 270 degrees C on heating. These are typical textures of the cholesteric liquid crystalline phase. (c) 2006 Wiley Periodicals, Inc.
Keywords: cholesteric liquid crystalline polymers (ChLCP); Differential scanning calorimetry (DSC); optical microscopy; solution polycondensation; Thermogravimetric analysis (TGA); viscosity